Analysis of Turnover Intention at PT Infia Media Pratama - Sukamdani, Nugroho B; Sukamdani, Hariyadi B; Sulistyadi, Yohanes; Hasibuan, Reyki Wahyudi (Journal of Applied Management Research, 2023)
PT Infia Media Pratama is a company based in the creative content industry, primarily social media content, which is currently experiencing a quite serious turnover rate, reaching an average of 19% in the last three years. Even though the normal turnover rate is 5%, to overcome this turnover problem, an analysis of the various variables that influence employee turnover intention is needed. This research aims to try to observe the relationship between the variables' employee engagement, quality of work life, organizational commitment, and employee turnover intention. The research was conducted through a survey using a census sampling method. Primary data analysis tests use multiple linear regression, and hypothesis testing uses t-test and F-test. The research results show that increasing employee engagement and organizational commitment have a positive influence on increasing employee turnover intention. The quality of work-life variable has a negative relationship with employee turnover intention, even though the effect is only 4%. Thus, companies need to improve the quality of work life in an effort to reduce employee turnover intention.